6
$\begingroup$

If $A$ is symmetric and $Y\sim\mathcal N(0,V)$, how can I show that $Y'AY\sim\sum_{i=1}^{t}(c_i * \chi^2(1))$ with 1 degree of freedom), where $c_i$ can be any scalar?

I multiplied out the canonical case where length($Y$) is two, and got $$ \begin{aligned} Y'AY &= [Y_1 Y_2] \left[\begin{array}{cc} a_{11} & a_{12} \\ a_{12} & a_{22} \\ \end{array}\right] \left[\begin{array}{cc} Y_1 \\ Y_2 \end{array}\right] \\ &= [Y_1 Y_2] [a_{11}Y_1 + a_{12}Y_2 ; a_{12}Y_1 + a_{22}Y_2] \\ &= a_{11} * Y_2^2 + 2a_{12}Y_1Y_2 + a_{22}Y_2^2 \end{aligned} $$ obviously the first and last term are chi-squared of degree 1, but the cross term? As $n$ increases (where the above example is $n = 2$), the cross terms increase as well.

$\endgroup$
1
  • 2
    $\begingroup$ Uncorrelate the $Y$s using Cholesky decomposition (say $Z = V^{-1/2} Y$); set up the quadratic form of interest in terms of the uncorrelated variables $Z$; solve the eigenproblem for the matrix in the middle; go back to $Z$s and rotate them using the orthogonal matrix made up of eigenvectors (which preserves their uncorrelatedness); look again at your quadratic form in terms of $Z$ and conclude that $c_i$ must be the eigenvalues of $AV$ or something like that. So they are not arbitrary. $\endgroup$
    – StasK
    Commented Oct 23, 2012 at 4:56

1 Answer 1

2
$\begingroup$

Perform eigen decomposition on $A = U \Lambda U'$ and let $X = U'Y$

$$Y' A Y = Y'U \Lambda U'Y = X' \Lambda X$$

(1) Show $X = U'Y = [x_1, x_2, ..., x_t]'$ is in multivariate normal distribution

First as Y is multivariate normal, X is also multivariate normal. $$E(X) = E(U' Y) = U' 0 = 0$$ $$Var(X) = U' Var(Y) U = U' U = I$$

So each $x_i$ is normally distributed.

(2) $X' \Lambda X = \lambda_1 x_1^2 + ... + \lambda_t x_t^2$

From (1), $x_i$ is normally distributed, then in $x_1^2, .. , x_t^2$, each is chi-square distributed with 1 df.

If you let $\lambda_i = c_i$, you will prove that $Y'AY = \sum_{i=1}^t c_i \chi^2(1)$

$\endgroup$
3
  • $\begingroup$ sorry, but how do you know that $U' Var(Y) U = U' U$? I guess you probably mean $Cov(Y)$ (the whole covariance matrix), but this was in the question defined as $V$ ... which would give you $U' V U$, but how can you then know that this is equal to $U' U$? $\endgroup$
    – Tomas
    Commented Jun 22, 2020 at 22:00
  • $\begingroup$ This proof is wrong - see stats.stackexchange.com/a/403940 for correct proof - and is missing some key part... and where do you have $V$? You completely ignore $V$ so it can't be correct. But anyway thanks for inspiration! It helped me indirectly. $\endgroup$
    – Tomas
    Commented Jun 25, 2020 at 14:33
  • $\begingroup$ @Curious you're right, the original proof is not correct, but can be corrected easily. You just eigen decompose V, say V = M * L * I * L' * M', where M is orthogonal matrix and L is a diagonal matrix. We will have L^(-1) M' Y ~ N(0, I). Next, observe Y'AY = Y' M L^(-1) * A * L^(-1) M' Y. Instead of decompose A, we can decompose (M L^(-1) A L^(-1) M'). The rest of the proof will follow now. Thanks again for pointing that out. $\endgroup$
    – zhanxw
    Commented Jun 26, 2020 at 0:47

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.